2011
DOI: 10.1159/000324702
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management and Symptom-Oriented Drug Therapy in Palliative Care

Abstract: Patients with advanced lifelimiting disease often suffer from symptoms that considerably impair their quality of life and that of their families. Palliative care aims to alleviate these symptoms by a multidimensional approach. Pharmacotherapy is an essential component. The objective of this review is to give an overview of symptomoriented drug therapy for the most important symptoms in palliative care. Leading symptoms that affect quality of life include pain, dyspnea, nausea and emesis, weakness and disorient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As the person's NCCD progresses, healthy eating guidelines recommended for the general population are no longer appropriate due to the effects of illness and treatment on the body and potential disturbances in appropriate food intake (Klein et al, 2011;Pilgrim et al, 2015). The aim of PFC in this stage of PC is to minimize food-related discomfort and maximize food enjoyment with respect to the individuals' caloric needs, and it should be accompanied by early identification of any food-related problem (Hutton et al, 2007;Boltong et al, 2014).…”
Section: Vertical Factorsmentioning
confidence: 99%
“…As the person's NCCD progresses, healthy eating guidelines recommended for the general population are no longer appropriate due to the effects of illness and treatment on the body and potential disturbances in appropriate food intake (Klein et al, 2011;Pilgrim et al, 2015). The aim of PFC in this stage of PC is to minimize food-related discomfort and maximize food enjoyment with respect to the individuals' caloric needs, and it should be accompanied by early identification of any food-related problem (Hutton et al, 2007;Boltong et al, 2014).…”
Section: Vertical Factorsmentioning
confidence: 99%
“…Symptom control has been the focus of most palliative care experts; symptom resolution following surgery is between 50% and 80%, emphasizing the fact that appropriate patient selection will yield optimal outcomes [ 24 26 ]. Indeed Miner suggested that symptom control should overshadow any attempts at improved survival [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 15%-70% of patients with cancer experience dyspnea (Dudgeon, Kristjanson, Sloan, Lertzman, & Clement, 2001;Joyce, 2010;Klein, Lang, Bükki, Sittl, & Ostgathe, 2011). The cause of dyspnea in patients with cancer may or may not be related to the cancer itself.…”
Section: Palliative Care and Dyspneamentioning
confidence: 99%
“…When patients are anxious, benzodiazepines are a treatment option (NCCN, 2013). If inflammation is present, corticosteroids may be ordered (Klein et al, 2011). The inflammation could be related to a malignancy, allergies, or noncancerous pulmonary conditions.…”
Section: Treatmentmentioning
confidence: 99%